A visual and reversible assay for temperature using thioflavin T-doped lanthanide/nucleotide coordination polymers. Issue 8 (24th March 2016) - Li, Yan-Yun; Jiang, Xiao-Qin; Zhang, Min; Shi, Guoyue
Abstract : A convenient one-step approach has been developed to make thermo-sensitive lanthanide coordination polymer nanoparticles (LCPNs) doped with thioflavin T. Abstract : In this work, we prepared a type of thioflavin T (ThT)-doped lanthanide/nucleotide coordination polymer by the self-assembly of ThT, europium ions (Eu 3+ ) and nucleotides (guanosine monophosphate, GMP) in aqueous solution ( i.e. ThT/Eu/GMP). The Eu/GMP coordination polymers show excellent adaptive inclusion properties for ThT in a convenient one-step approach, which can readily enhance the fluorescence of ThT via the restricted effect. Moreover, the as-prepared hydrophilic ThT/Eu/GMP coordination polymers have the capability to act as a temperature-sensitive, visual and reversible sensor in aqueous solution under the irradiation of visible light. Our proposed design is cost-effective and simple to prepare without chemical modification or fluorescence labeling.